الاقتصاد الأزرق: قراءة مفاهيمية مع عرض تجارب دولية وعربية ناجحة: The Blue Economy: A conceptual reading with a presentation of successful international and Arab experiences - بودية فاطمة (Journal of North African Economies, 2025)
This research aims to define the concept of the blue economy and its various fields and economic activities associated with it, in addition to its relationship to sustainable development and the challenges facing it because it is newly emerging. In addition to highlighting some international and Arab experiences that have achieved great success in many fields related to it. Therefore, the research problem was as follows: What is the blue economy? How did countries benefit from it in developing their economies? To address the problem, the research was divided into the following axes: The first axis: The conceptual framework of the blue economy. The second axis: The blue economy: a major growth engine - presenting successful international and Arab experiences -. Among the most important results that have been reached is that the concept of the blue economy is still relatively new in use, and it includes a new vision for the economic exploitation of ocean resources, lakes, rivers and other water bodies, and it also constitutes a real opportunity for countries of the world to protect their biodiversity and maintain their security. food and climate, and the diversity of its sources of income